Implikasi Teori Behavioristik dalam Kegiatan Pembelajaran di Sekolah - Rizky Allivia Larasati Haibar; Yuzarion Yuzarion; Junaidi Junaidi (Universitas Ahmad Dahlan, 2021)
The Implications of Behavioristic Theory in Learning Activities in Educational InstitutionsBehavioristic learning theory is a learning theory that is widely applied in the learning process in Indonesia. In this theory, the change in behavior shown by students is the main indicator as a result of stimuli and responses. Students who are able to show a response in the form of behavior change are successes in the learning process. Behavioristic learning theory has a main characteristic, namely the teacher is authoritarian who acts as a controller, while students are passive and depend on the stimulus provided by teacher. The aim of applying behavioristic learning theory is so that student behavior changes as a form of response to a better direction. According to this theory, changes in behavior as a desired response will be stronger if reinforcement is given. Likewise, the unwanted response will disappear when given a punishment. This article describes the concept of behavioristic learning theory and its applications and implications in education. Behavioristic learning theory is believed to be able to bring out good behavior in students.